Mobile App for Soundscape evaluation for the Spanish speaking community validated through principal component analysis - Useche, Jorge Eduardo; Rodríguez, Belman Jahir; Guevara, Andrés Felipe; Romero, Jhoan Sebastián; Herrera , Marcelo; Hermida, Luis Fernando (TECCIENCIA, 2023)
Soundscapes represents the way in which people perceive and experiment the sounds of a particular acoustic environment. In this paper we explain the procedure carried up to develop a Mobile App for the evaluation of soundscapes in the case of Spanish speakers and its validation through principal component analysis. The application (called "SSEBOG") was implemented for android devices, and it is based on the ISO 12913-2 standard. The application allows geolocation, audio recording, image capture, feedback to users and data processing. A pilot test over a group of 56 persons evaluating the same acoustic environment was carried up with the App. The results of the principal component analysis indicate that the translations propose are consistent with the circular pattern model for the classification of the soundscapes frequently used for English speakers, however, the results suggest that the meaning of the diagonals in the circular pattern model does not correspond to a simple translation to Spanish.